Research on the Relationship between Corporate Social Responsibility and Financial Performance of Chemical Companies - Zhang, Hongtao; BI, Chuanchen (Technium Social Sciences Journal, 2022)
With the continuous development of social economy, the issue of corporate social responsibility has received extensive attention. At present, many companies directly incorporate social responsibility into their development and operations, and more and more companies have also begun to publish social responsibility reports to disclose their social and environmental information. According to a KPMG survey report, more than 75% of about 4,500 companies in 45 countries and regions around the world have released social responsibility reports. However, the regulatory authorities have not made mandatory requirements on the form of corporate social responsibility report information disclosure, and social responsibility information disclosure is a voluntary behavior of enterprises. It can be found from the social responsibility reports released by companies that most companies selectively disclose positive social responsibility information, but seldom disclose relatively negative social responsibility information in their reports, resulting in a low quality of corporate social responsibility reports. Then, the existing literature has not given a clear answer on the quality of information disclosure in corporate social responsibility reports and what impact it will have on financial performance. In this research, we would trying to find some evidence to answer this question.